A Qualitative Study Exploring Community Pharmacists' Experiences and Views About Weight Management Interventions and Services in Klang Valley, Malaysia - Verma, Rohit Kumar; Chong, Wei Wen; Taha, Nur Akmar; Paraidathathu, Thomas (Frontiers in Public Health, 2021)
Objective: To qualitatively explore the perspectives of community pharmacists in Malaysia on their roles in weight management, and the barriers and facilitators in the expansion of these roles. Methods: Semi-structured individual interviews were conducted with community pharmacists in Malaysia with a validated interview guide from May 2018 to January 2019. The interviews were conducted in person (face-to-face). All interviews were audio-recorded with consent and transcribed verbatim. The interview transcripts were analyzed thematically, whereby emerging themes were coded and grouped into categories. Results: Twenty-four community pharmacists with length of time in pharmacy practice ranged from 2-40 years were recruited. Participants described their perceptions on the different weight management interventions where they emphasized the importance of comprehensive lifestyle intervention and viewed that it should be the first line intervention. Participants regarded their weight management service as easily accessible or approachable since community pharmacies are often the first point of call for patients seeking advice for their conditions before consulting doctors. Barriers identified by community pharmacists in were mainly organizational in nature, which included lack of private consultation room, lack of time, and lack of qualified staff. Participants also described the needs for training in weight management. Conclusion: Community pharmacists in Malaysia believed that they can positively contribute to the area of weight management. They cited multiple roles that they could play in weight management interventions and services. However, barriers would need to be addressed to strengthen and improve community pharmacists’ roles and contributions in weight management service.